The Importance of the Ansoff Matrix for the Study of the Information Services Market - Pereira Ferraz Soares Ferreira, Ana Patrícia; Marques, Maria Beatriz Pinto de Sá Moscoso (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2024)
The purpose of this research is to present the matrix developed by H. Igor Ansoff and reflect on its usefulness for studying the Information Services (IS) market in the context of the information and knowledge society of the 21st century, whose environment is infopolluted and constant changing, making it difficult to access up-to-date, useful, and quality information that would meet the needs of both individuals and organizations. The research was carried out by identifying and consulting scientific literature through EBSCO. The search terms used were Ansoff Matrix, Marketing, Information Science, and Information Services. The chronological period from 1957 to 2023 and the languages Portuguese and English were selected. The results show that information is a valued asset in the 21st century because, together with the Ansoff Matrix, it allows us to understand market needs and create information products and services that help meet consumers' information needs, but also to value and recognize the work done by information services. The Ansoff matrix helps us to understand the best strategy to apply to an information service so that it develops and evolves, contributing to the knowledge and development of the individual and/or organizational consumer, playing an essential role in the innovation and renewal of information products and services. We conclude that in the context of the Information and Knowledge Society, the value of information for human development will contribute to a more informed and, therefore, happier society.